Strategi Pundi Sumatera dalam Mendukung Kehidupan Perekonomian SAD di Sepanjang Lintas Tengah Sumatera - Safitri, Elvina (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2020)
This study aims to determine what strategies are carried out by the Pundi Sumatera in supporting the economic life of Suku Anak Dalam (SAD) along the central Sumatera cross, especially in the phase II SUDUNG Program. The selection of research on the Pundi Sumatera strategy in the Phase II SUDUNG Program was due to this stage where the involvement of local governments in program implementation had an increasingly large portion. The method used in this research is qualitative method. The research background is located in the Central Sumatera region, including Jambi Province, Merangin Regency, West Sumatra Province, namely Dharmasraya Regency. Data collection techniques used were observation, interviews and documentation. Data taken through informants. The stages in analyzing the data are: reduction, presentation of data and making conclusions. The results of this study indicate that the strategy undertaken by the Pundi Sumatera has been good, namely by involving various parties, especially the government, local communities and other parties so that the program to support the economy of SAD in the area can be implemented.